3(x-5)-2x=7(x-13)-2(3x-40)

Simple and best practice solution for 3(x-5)-2x=7(x-13)-2(3x-40) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-5)-2x=7(x-13)-2(3x-40) equation:



3(x-5)-2x=7(x-13)-2(3x-40)
We move all terms to the left:
3(x-5)-2x-(7(x-13)-2(3x-40))=0
We add all the numbers together, and all the variables
-2x+3(x-5)-(7(x-13)-2(3x-40))=0
We multiply parentheses
-2x+3x-(7(x-13)-2(3x-40))-15=0
We calculate terms in parentheses: -(7(x-13)-2(3x-40)), so:
7(x-13)-2(3x-40)
We multiply parentheses
7x-6x-91+80
We add all the numbers together, and all the variables
x-11
Back to the equation:
-(x-11)
We add all the numbers together, and all the variables
x-(x-11)-15=0
We get rid of parentheses
x-x+11-15=0
We add all the numbers together, and all the variables
-4!=0
There is no solution for this equation

See similar equations:

| 10.26+1.9q=q | | 36y-8=4(9y-2) | | x=5x^2+20x+19 | | -6=1/3(-10x) | | 0.14(y-6)+0.18y=0.02y-0.03(50) | | 4r+2r-3r=27 | | 1/7⋅x=1 | | 0=4x-7/3 | | 1+11=-3(3x-4) | | 17=2-3b | | 6v+12=3(v-1) | | 15/x=5/32 | | -2(7-y7+4=-4 | | 7(4v-5)=33-6v | | 43/2b+45=540 | | 6v+12=3(v—) | | 6v-45=-3(v-9) | | 6r=-108 | | 2x+4-x=15 | | 5(2x-8)-x=7x-38 | | -6x+1+5x=1x | | 7n+1=71 | | 1-7x+4x=-20 | | 6x-2(x+9)=-3(x-1) | | 7m-4-9m-36=-10 | | 29=u/2+12 | | 200m−100m+48500=51250−150m | | 4-8=3-n/3 | | -3n+15=24 | | 7(m+13)+17=3 | | 20-15j=-20-5j-20 | | 4x+-8=32x |

Equations solver categories